2006
DOI: 10.1186/1297-9686-38-5-479
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic assessment of a Thyroglobulin marker for marbling in beef cattle

Abstract: -A meta-analysis was undertaken reporting on the association between a polymorphism in the Thyroglobulin gene (TG5) and marbling in beef cattle. A Bayesian hierarchical model was adopted, with alternative representations assessed through sensitivity analysis. Based on the overall posterior means and posterior probabilities, there is substantial support for an additive association between the TG5 marker and marbling. The marker effect was also assessed across various breed groups, with each group displaying a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Polymorphism in the thyroglobulin gene was not associated with backfat thickness in the present data (p > 0.05) and the allele described as favorable for high marbling (Barendse et al, 2001), designated in that study as allele 1, was found in the Canchim breed at a frequency of 16.33 % (Table 1), which is not low. The polymorphism in the 5´ leader sequence of the thyroglobulin gene was associated with intramuscular fat deposition in beef cattle (Barendse et al, 2001;Gan et al, 2008;Wood et al, 2006) and Casas et al (2005) found association of this polymorphism with fat thickness in a Brahman population, but not with marbling score; however, it could not be concluded that there was a direct effect of the TG gene on that work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphism in the thyroglobulin gene was not associated with backfat thickness in the present data (p > 0.05) and the allele described as favorable for high marbling (Barendse et al, 2001), designated in that study as allele 1, was found in the Canchim breed at a frequency of 16.33 % (Table 1), which is not low. The polymorphism in the 5´ leader sequence of the thyroglobulin gene was associated with intramuscular fat deposition in beef cattle (Barendse et al, 2001;Gan et al, 2008;Wood et al, 2006) and Casas et al (2005) found association of this polymorphism with fat thickness in a Brahman population, but not with marbling score; however, it could not be concluded that there was a direct effect of the TG gene on that work.…”
Section: Resultsmentioning
confidence: 99%
“…The thyroglobulin gene (TG) was mapped in this region (Threadgill et al, 1990) and it has been indicated as a candidate gene for fat deposition traits in beef cattle (Barendse et al, 2001;Gan et al, 2008;Casas et al, 2005 andWood et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This result could be due to the rearing period being too short (<250 days) or other factors. Wood et al, in their meta-analysis based on 11 papers, indicated that there was a positive association between the polymorphic forms of TG5 and the degree of meat marbling [ 72 ]. A significant relationship between beef quality and TG5 for Charolaise and Angus cattle was also determined by Van Eenennaam et al [ 73 ].…”
Section: Thyroglobulinmentioning
confidence: 99%
“…Beef industry is looking for gene markers that would identify animals that have a high propensity to accumulate intramuscular fat in order to produce tasty and tender meat 1 . To finding the candidate genes of intramuscular fat deposition, traditional QTL analysis was used based on position dependent strategy such as thyroglobulin (TG), fatty acid binding protein 4 (FABP4), or growth hormone 1 (GH1) 2 - 4 . Recently, several strategies have been developed to break the restriction of information bottleneck of the traditional candidate gene approach.…”
Section: Introductionmentioning
confidence: 99%